Antibody-drug conjugate therapies in multiple myeloma-what's next on the horizon? - Monique Hartley-Brown; Paul Richardson (Open Exploration Publishing Inc., 2022)
Targeted immunotherapy has arisen over the past decade to the forefront of cancer care. Notably, targeted therapies such as antibody-drug conjugates (ADCs) are becoming more recognized for a novel approach in cancer treatment. The mechanism of action of ADCs incorporates a monoclonal antibody portion directed against the tumor cell antigen and attached to the tumoricidal portion via chemical linkage. The binding of the monoclonal antibody portion allows for tumor cell internalization of the ADC and precise release of the toxic payload within the cancer cell. Multiple myeloma (MM) is an incurable cancer for which belantamab mafodotin was the first-in-class ADC to achieve United States Food and Drug Administration (FDA) approval for treatment of this disease. Clinical trials are currently evaluating other ADCs in the treatment of MM. In this review, a look at the current ADCs being tested in MM clinical trials with a focus on those that are more promising and a potential next-in-line for FDA approval for treatment of MM is discussed.